Identification of causative agent for fungal infection and effect of disinfectants on hatching and survival rate of common carp (C. carpio) larvae - Yeasmin, Syeda Maksuda; Rahman, Md Anisur; Hossain, Md Mer Mosharraf; Rahman, Md Habibur; Asif, Abdulla Al (Asian Journal of Medical and Biological Research, 2016)
Common carp (Cyprinus carpio) is one of the commercially important and commonly cultured fish. In the hatchery intensive incubation leads to microbial overgrowth in C. carpio eggs that hamper egg development, hatchability and larval survivability. The aim of this study is to find out causes of mass mortality in C. carpio eggs during peak- breeding season between March to May 2015 at Mafatema fish hatchery, Chanchra, Jessore sadar upazilla. In the present study three disinfectants with three different concentrations in each such as methylene blue 1, 3 and 5mg/L., malachite green 1, 3 and 5mg/L., sodium chloride 1, 2 and 3g/L were used to observe the hatching rate of fertilized eggs and survival rate of larvae. Bacterial load of culture water was examined during the induced breeding of C. carpio with mycological examination of egg samples with different disinfectants. The total bacterial count fluctuated from 3.4 x 108 CFU/ml to 32.7 x 108 CFU/ml during the period of fertilization to 4days of hatching. The fertilized eggs infected by Saprolegnia spp. were appeared as tuft hairy like balls with a white cottony envelop. Among all the treatment 1mg/L methylene blue, 3mg/L malachite green and 1g/L sodium chloride showed significantly better (P<0.05) hatching rate 95·33±2·08, 88.00±2.64 and 92.33±4.04% respectively. The same concentration of methylene blue, malachite green and sodium chloride showed significantly better (P<0.05) better survival rate 95·00±4.35, 75.00±3.00 and 87.00±6.24% respectively. Finally among all the treatment 1mg/L of methylene blue showed significantly better (P<0.05) hatching and survival rate 95·33±2·08% and 95·00±4.35 % respectively. So 1mg/L of methylene blue is the best disinfectant for C. carpio fertilized egg treatment. Asian J. Med. Biol. Res. December 2015, 1(3): 578-588